Identifying Bioactive Ingredients and Antioxidant Activities of Wild Sanghuangporus Species of Medicinal Fungi - Hao Wang; Jin-Xin Ma; Dong-Mei Wu; Neng Gao; Jing Si; Bao-Kai Cui (Journal of Fungi, 2023)
Sanghuangporus refers to a group of rare medicinal fungi with remarkable therapeutic properties. However, current knowledge on the bioactive ingredients and antioxidant activities of different species of this genus is limited. In this study, a total of 15 wild strains from 8 species of Sanghuangporus were selected as the experimental materials for identification of the bioactive components (polysaccharide, polyphenol, flavonoid, triterpenoid, and ascorbic acid) and antioxidant activities (scavenging activities against hydroxyl, superoxide, DPPH, and ABTS radicals; superoxide dismutase activity; and ferric reducing ability of plasma). Notably, individual strains contained different levels of various indicators, among which Sanghuangporus baumii Cui 3573, S. sanghuang Cui 14419 and Cui 14441, S. vaninii Dai 9061, and S. zonatus Dai 10841 displayed the strongest activities. The correlation analysis of bioactive ingredients and antioxidant activities revealed that the antioxidant capacity of Sanghuangporus is mainly associated with the contents of flavonoid and ascorbic acid, followed by polyphenol and triterpenoid, and finally, polysaccharide. Together, the results obtained from the comprehensive and systematic comparative analyses contribute further potential resources and critical guidance for the separation, purification, and further development and utilization of bioactive agents from wild Sanghuangporus species, as well as the optimization of their artificial cultivation conditions.